Recurrent miscarriage in a woman with congenital factor V deficiency: a case report - Mohammad Shirzadi; Amir Hossein Radfar; Mehdi Dehghani (BMC, 2022)
Abstract Background Factor V deficiency is a rare bleeding disorder that can be either congenital or acquired. Factor V deficiency mostly present with mucosal bleeding. Coagulation factor V does not increase considerably during normal gestation. Since pregnancy can be threatened by blood clotting disorders, abnormal changes in coagulation factors level can pose challenges to pregnant women. Case presentation We report a 40-year-old pregnant woman with prolonged gingival bleeding and epistaxis at 28 weeks of pregnancy. Her past medical history included two unexplained abortions. Physical examination was unremarkable, but the blood test showed elevated PT and PTT with a considerable decrease in factor V activity, while other factors were within normal range. Subsequently, the patient was diagnosed with congenital factor V deficiency. After treatment with fresh frozen plasma, she underwent vaginal delivery and a baby with factor V deficiency was born. Conclusions This is the second report of recurrent miscarriage in congenital factor V deficiency patients. Clinicians should consider the possibility of factor V deficiency in women with a history of idiopathic miscarriage even in patients without any symptoms.